The Causality Between Remittances, Debt Services and Economic Growth of Lao PDR - THEPMAYTHY, Thipphaphone; HER, Pheng; PHENGSAVAT, Sitthivikone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study to determine the causal direction among remittances, debt service, and economic growth using the Granger causality test within the Vector Autoregression (VAR) model framework. It uses time-series data from 2000 to 2024, which are taken from the World Development Indicators (WDI) of the World Bank and the Sustainable Development Goal (SDG) Country Profile databases. The empirical analysis shows that, in the growth equation, past economic growth ((Growth t-1) has a statistically significant positive effect at the 0.01 level, with a coefficient of 0.6415, indicating growth persistence. Conversely, past remittances (REM t-1) have a statistically significant negative effect at the 0.05 level with a coefficient of -0.8277, and past debt servicing (DS t-1) also has a statistically significant negative effect at the 0.01 level on growth. In the remittance equation, (REMt-1) shows a strong positive significance with a coefficient of 0.8695, while and are statistically insignificant. In the debt servicing equation. exerts a statistically significant positive influence at the 0.01 level, with a coefficient of 0.7732, while (REM t-1) and (Growth t-1) remain insignificant​. The Granger causality test indicates that both remittances and external debt servicing have causal relationships with economic growth, but there is no evidence supporting causality in the opposite direction. This implies a unidirectional causality, where external financial flows (remittances and debt servicing) influence economic growth, but not the reverse – from growth to remittances or debt servicing.